Tertiary‐Alcohol‐Directed Functionalization of Remote C(sp3)−H Bonds by Sequential Hydrogen Atom and Heteroaryl Migrations. (12th January 2018) - Wu, Xinxin; Wang, Mingyang; Huan, Leitao; Wang, Dongping; Wang, Jinwei; Zhu, Chen
Abstract: Reported for the first time is a tertiary‐alcohol‐guided heteroarylation of remote C(sp 3 )−H bonds. The mild and direct generation of alkoxyl radicals from alcohols is enabled by visible‐light photocatalysis. A remote hydrogen atom and heteroaryl migration sequence are involved in the reaction. Many sensitive groups remain intact in the reaction, thus illustrating wide functional‐group compatibility. This protocol provides a practical strategy for the late‐stage modification of alkyl ketones.